Handbook of Patristic Exegesis : Part I: The Bible in Ancient Christianity - Kannengiesser, Charles (Biblical Studies, Ancient Near East and Early Christianity - Book Archive 2000-2006., 2004)
Through this Handbook of Patristic Exegesis , the reader will obtain a balanced and cohesive picture of the Early Church. It gives an overall view of the reception, transmission, and interpretation of the Bible in the life and thought of the Church during the first five centuries of Christianity, the so-called patristic era. The handbook offers the context and presuppositions necessary for understanding the development of the interpretative traditions of the Early Church, in its catechesis, its liturgy and as a foundation of its systems of theology. The handbook presents a comprehensive overview of the history of patristic exegesis. Apart from a general introduction to the major topics in this field, it contains essays by leading patristic scholars on the most important Church Fathers, such as Augustine, Irenaeus, Origen, Gregory of Nyssa, and others. The essays are supplemented by bibliographies of editions and studies on patristic exegesis published from 1945 until 1995. Together, these bibliographies form the only comprehensive bibliography presently available on this topic. The print edition is available as a set of two volumes (9789004098152).